Energy absorption characteristics of sandwich structures subjected to low-velocity impact - Foo, Choon Chiang (2009)
This dissertation presents experimental, numerical and analytical investigations of sandwich plates subjected to quasi-static loading and low-velocity impact. The objectives of this research are to predict the low-velocity impact response and damage in a sandwich structure, and to characterise the energy absorbed by the structure. Aluminium sandwich plates and composite sandwich plates made of Nomex honeycombs and carbon/epoxy skins were investigated under both static indentation and low-velocity impact loadings using a hemispherical indentor/impactor. Emphasis was placed on the damage characteristics and the energy absorption capabilities of these structures. Based on the least-squares method, a single equation that links absorbed energy with the impact energy and the damage initiation threshold energy was derived for composite sandwich plates. It was found that the proportion of impact energy absorbed by the composite plate was inversely related to the damage initiation energy, but directly related to the relative loss of the plate’s transverse stiffness after damage. This energy equation is useful for further studies on damage resistance and tolerance. A three-dimensional FE model was also developed to simulate the indentation and impact tests. In contrast to the equivalent continuum core normally used by other investigators, the cellular honeycomb core was discretely modelled with shell elements so that it was geometrically more accurate. A progressive damage model was also included to predict damage initiation and progression in the laminated skins. Comparison of numerical results with test results demonstrated the ability of the model to capture the impact characteristics. Core damage was identified to be one of the damage mechanisms at initial damage. Parametric studies also showed that denser cores resulted in greater peak loads and smaller damage proﬁles in the impacted structure. However, the energy absorbed during impact was independent of the core density. Finally, an analytical model was proposed to predict the impact response of a sandwich structure beyond the onset of damage. Closed-form solutions were derived for three parameters that described the plate’s structural behaviour, namely, the plate’s elastic structural stiffness, the critical load at the onset of damage, and the reduced stiffness after damage. The critical load was found to be theoretically predictable by accounting for the elastic energies absorbed by the sandwich plate up to core failure. These parameters were then included in a modified energy-balance model coupled with the law of conservation of momentum to predict transient load and deflection histories for the plate subjected to impact. This impact model is an eﬃcient design tool which can complement detailed FE simulations.